World prices and inflationary process in a small open-economy - case of Ireland - Geary, Patrick T. (Economic & Social Studies, 1976)
The standard wage-price model of inflation and a variant of Parkin's (1973) inflation model, both directly incorporating world prices, are applied to the Irish economy for the period 1953-74. This approach does not allow the inflationary transmission mechanism to be investigated in detail; it restricts attention to the proximate role of world prices as a determinant of Irish inflation. The models are estimated using annual data and the coefficient restrictions implied by the theory of small open economy inflation are tested. When world prices are measured by the UK Retail Price Index, these restrictions are satisfied although the individual coefficients raise some questions. The Personal Consumption Deflator of the OECD yields less satisfactory results. The weak relationship between unemployment and wage and price inflation, a feature of other studies of Irish inflation, is also found in this study.
Keywords: Economics; Wage price model